Pengaruh Penggunaan Media Video Animasi Terhadap Hasil Belajar Matematika Kelas IV SD - Dita Wahyuni; Wella Asmada Yanti; Zura Vazira (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This article discusses a study which aims to determine the effect of using animated video media on mathematics learning outcomes in class IV students at SDN 01 Air Tawar Barat. The research used in this research is a quasi-experiment in the form of a Post-test Only Control Group research design. This design involves 2 classes, namely class IV A as a control class with 32 students and class IV B as an experimental class with 32 students. The data collection process was carried out by giving a post test to the two classes. To determine the research results, the T test formula is used. The determination of Ho is rejected if Tcount > Ttable and Ho is accepted if Tcount < Ttable. The results of the calculation test in the research stated that Tcount was 7.391 and Ttable was 1.999 at a significance level (α) of 0.05. Because Tcount > Ttable is 7.391 > 1.999, it can be concluded that there is an influence of the use of animated video media on mathematics learning outcomes for class IV students.